ANALYSIS PROBLEMATICS OF ILLEGAL PARKIRNG IN TANAH ABANG MARKET CENTRAL JAKARTA - Nasyar, Noor Muhammad; Harsasto, Priyatno; Adnan, Muhammad (Journal of Politic and Government Studies, 2016)
Analysis problematics of illegal practice in Tanah Abang Market Central Jakarta has apurpose to find out why the practice of illegal parking in Tanah Abang Market could persistuntil today, when it was often obtain enforcement of formal institutions that deal with theseillegal parking. Another aim is to determine wheter there is a local strongman in the illegalparkirng so that activities can continue and secure until today.Methods of execution in this research use qualitative descriptive research with primary datatypes are the words and actions. Sources of data obtained derived from primary andsecondary data. To search for informants in this study is conducted with a purposive sample(making intentional) and accidental sampling (sampling by accident when he met at the studysite). Techniques for collecting data using interview, observation and documents.The practice of illegal parking in Tanah Abang Market is one of the problems that have beenaround a long time in this area. Illegal parking is the case in areas that already have a ban onparking. Illegal parking makes the area more often jammed, irregular, and rundown. Variouspolicies have been issued by Department of Transportation and Transport Jakarta in dealingwith this case, but still no result has yet effective way to reduce this illegal parking. Dept ofTransportation and Transport Central Jakarta City Administration has also done various waysand methods to combat this illegall parking. The result are still the same and there has beenno change that we can see. Illegal parking practices are able to continue to survive and carryout daily activities. This activitiy is certainly a negative impact on the face of Jakarta as thecapital city of Indonesia.Keywords :Analysis, Illegal Parking Practice, and Tanah Abang Market